Cyberbullying among adolescents : bullies and victims associated with parental relations, online usage time and gender differences - Nína Björk Gísladóttir 1990- (2016)
With increased technology, easier access of information, and faster communication ways, a new type of bullying has been rising globally labeled cyberbullying. Cyberbullying is common and harmful among adolescents that can have extensive consequences. Whereas cyberbullying often happens in adolescent’s homes, the aim of current study was to examine parental relations and online usage time and see these factors might have influence on both cyber-bullies and cyber-victims. The study used archival data from the Icelandic Centre for social Research and Analysis (ISCRA), Youth in Iceland 2014. Random sample consisted of 2.017 participants was used from a population of 11.013 Icelandic secondary school students. Participants were 14-16 years old. Logistical regression was used in the study and results indicated that low parental support and frequent online usage time increased the likelihood of becoming a cyber-bully or a cyber-victim. Parental monitoring did show significant relation to cyber-bullies but not to cyber-victims. Furthermore, females were more likely to become cyber-bullies and cyber-victims. Keywords: Adolescents, cyber-bullies, cyber-victims, parental support, parental monitiring, online use, gender Með aukinni tækni, auðveldara aðgengi að upplýsingum og hraðari samskiptaleiðum, hefur ný gerð af einelti vaxið á heimsvísu kallað neteinelti. Neteinelti meðal unglinga er algengt og skaðlegt sem getur haft í för með sér alvarlegar afleiðingar. Þar sem neteinelti á sér oftast stað á heimilum unglinga, var tilgangur rannsóknarinnar að skoða hvort stuðningur og eftirlit foreldra ásamt tíma eyddum á internetinu hafi áhrif á það hvort að börn þeirra verði gerendur eða þolendur neteineltis. Í rannsókninni voru notuð fyrirliggjandi gögn frá Rannsóknir og greining, Ungt fólk 2014. Alls voru 2017 þátttakendur valdir tilviljunarkenndu úrtaki út heildarþýði 11.013 grunnskólanema. Nemendur voru 14-16 ára. Aðhvarfsgreining hlutfalla var notuð við úrvinnslu gagna og leiddu niðurstöður í ljós að lítill stuðningur ...